PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - B51110078, Julia Paramita (Jurnal KIAFE, 2014)
Intellectual capital (IC), these days, has a key role in the effort to increase the value of various companies. This is due to the awareness that IC is a platform for companies to be more competitive. The purpose of this study is to investigate the relation between intellectual capital and fimrs market value and financial performance. By using Pulic"™s- Value Added Intellectual Capital (VAIC), this research examine the relationship between the efficiency of value added (VAIC) by three major component of firms resources (physical asset, human capital, and structural capital) and firms market value (MtBV) and explore the relation between intellectual capital and financial performance (ROA, ROE, and EP). Data are drawn from 15 listed firms in Indonesia Stock Exchange in 2010 until 2012. Data analysis using multiple regression. The result show that intellectual capital influences negatively to firms market value but intellectual capital influences positively to financial performance (ROA, ROE, and EP). Keyword : Intellectual capital (IC), market to book value (MtBV), financial performance, ROE, ROA, EP